A new small Arthroleptis (Amphibia: Anura: Arthroleptidae) from the Liberian part of Mount Nimba, West Africa - Rödel, Mark-Oliver; Doumbia, Joseph; Johnson, Alex T.; Hillers, Annika (Zootaxa, 2009)
A new small West African Arthroleptis from the rainforest at the south-eastern tip of Mount Nimba, Liberia is described. The new species differs from all known congeners by the combination of a unique color pattern, a rounded canthal region and a completely smooth skin. The comparison of 592 base pairs of the mitochondrial 16S rRNA from the new species with Arthroleptis samples from all over West Africa, revealed genetic distances between 13.4–17.9%. From the morphologically similar A. aureoli the new species differed by 17.9%. Future research may reveal the necessity to establish a new genus for this peculiar new frog.